Spatio-Temporal Analysis of Land Surface Disturbance and Soil Degradation in and around the Iron Ore Quarry in Al-Jumum Using Remote Sensing and GIS (The International Journal for Scientific Research, 2026)
This study analyzes the spatio-temporal change in land surface disturbance and soil degradation in and around the iron ore quarry in Al-Jumum Governorate during 2015–2025 using Landsat Collection 2 Level-2 data, remote sensing, and geographic information systems. The Disturbance Index (DI) and Bare Soil Index (BSI) were used to derive comparable quantitative indicators within the quarry boundary and a 3 km surrounding buffer. The results indicate persistent surface disturbance within the mining core, where the maximum DI increased from 1.385 in 2015 to 1.481 in 2025, while the mean value declined from 0.872 to 0.812, reflecting intensified disturbance in the core and relative stability in the surrounding area. BSI results also reveal continued soil exposure and the extension of high-exposure zones beyond the official quarry boundary, particularly toward the south. The study demonstrates the value of multi-index spatio-temporal analysis for monitoring mining sites in arid environments and supports expanding environmental impact assessment beyond official license boundaries.
Keywords: Land Surface Disturbance; Soil Degradation; Iron Ore Quarry; Disturbance Index; Bare Soil Index; Remote Sensing; GIS